Enhancing collaboration for future halal studies graduate employability - Ibrahim, Muhammad Irhammudin; Jamaludin, Mohammad Aizat; Zubairi, Ainol Madziah; Muflih, Betania Kartika; Hashim, Yumi Zuhanis Has-Yun (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2022)
The halal industry development requires a competent halal industry human capital. However, very few establishments create employment opportunities for halal studies graduates. There are currently no guidelines or frameworks for halal education to suit the job markets. In response to this scenario, this paper will examine the support system of the Malaysian higher learning institution that offers halal studies programmes to develop a more comprehensive halal education ecosystem framework. Additionally, the study examined whether Malaysia’s current legal system has resulted in increased job opportunities for halal studies graduates. On 12th April 2021, the Malaysian Qualifications Agency (MQA) in collaboration with Halal Development Corporation Berhad (HDC) and the Ministry of Higher Education (MOHE) has, developed the new academic programme standard for halal studies. Is this standard necessary to alter the current halal studies curriculum to make it more relevant to the halal industry? Thus, it is necessary to thoroughly study and discuss the vibrant guidelines and framework to enhance the quality and competency of halal studies graduates for the future job markets in Malaysia, which serves as a hub for competent halal expert providers that capable of meeting the halal industry ecosystem’s human capital needs.